(Re)vision of Religious Education of Children and Youth in Secularized Polish Society - Zellma, Anna (Verbum Vitae, 2024)
Rapidly progressing multifaceted secularization processes in Polish society strongly influence the shape of religious education of children and adolescents in the school environment. They determine a number of dimensions of the social and mental activity of young people. Their effects are visible, especially in the attitudes of children and youth to God, the Church, religious lessons, moral norms, and religious practices. This situation raises new challenges for the religious education of the young. Reading this as a “sign of the times,” this article revises religious education in Polish schools. The need to reorganize the model of religious education lessons and to introduce changes in the curricular assumptions of religious education teaching, in student textbooks and methodological guides is pointed out. Pre-evangelization and educational activities, resignation from the mere transfer of religious knowledge, and the development of preconceived skills and attitudes are considered important. The author emphasizes the value of providing opportunities for the construction of knowledge and for the student’s own engagement during religious education lessons. In this context, much attention is paid to the role of the religious education teacher, who is to be first and foremost a companion on a journey, an educator and a witness of faith, open to new challenges, able to communicate effectively with students, creative, and tolerant. The right personality traits of the religious education teacher and their multiple competencies (including communicative and interpersonal ones) play a key role in religious education. They guarantee the effectiveness of communication within a group of religious lesson participants. They foster authentic interpersonal relationships and community-building, thus meeting the natural needs of young people. In practice, they require a paradigm shift in the formation of religious education teachers.